Herbal Supplements: Can They Cause Hypomania? - Kazi, Sana Elham (Cureus, 2021)
Herbal medication use is prevalent and increasing in the general population. A comprehensive review of complementary and alternative medicine use including herbal medications and supplements is often overlooked by physicians. Patients generally believe that all herbal products are safe without any side-effects. Herbal medications may have complex pharmacodynamics and can be associated with various psychiatric symptoms. The general population, as well as physicians, may be unaware of the risks and side-effects associated with herbal supplement use and further research may be needed. The objective is to describe a case report of acute onset of symptoms of hypomania associated with the increasing use of herbal supplements. A 49-year-old man developed symptoms of hypomania after a two-month history of daily use of a combination of more than 25 herbal supplements and daily cannabis use. Hypomania symptoms were temporally associated with the use of multiple herbal supplements that included ginseng. We recommend that a thorough history of medication use including herbal supplements and other alternative medications and a collateral report from family members and other providers including herbalists be obtained on all patients presenting with psychiatric symptoms. Further research is needed to identify the pharmacodynamics, risks, and adverse effects, and drug and food interactions of each herb.